صور الرهبة في شعر النابغة الذبياني - مودع, سليمان (Sciences humaines; Vol. 32 (2013): SCIENCES HUMAINES)
سعت هذه الدراسة لإبراز ما للصورة من دور في تجسيد الأفكار و الأشياء، من خلال تداولها في العلاقات التواصلية.ولقد كانت السيمياء مرتكزا ومعينا في هذا البحث الموسوم  بـ " صور الرهبة في شعر النابغة الذبياني" . ولقد تم التركيز على التصوير الأدبي كإستراتيجية لرصد جمالية  تصوير الرهبة في الخطاب الشعري للنابغة الذبياني ، وهذا من تآزر العناصر الجزئية البانية  للصورة، فينقلب الدال الحسي المستلهم  من الطبيعة إلى دال جديد، يحاول أن يأخذ بتمظهره في تشكله الجمالي شكلا جديدا، و لونا جديدا، ومعنى جديدا أيضا . ولقد تمكن الشاعر من فنه فرصد لحظات الضعف الإنساني، فسبر و صور خلجات نفسه، ونبض قلبه، و جعل الصورة حية من تعاقب عناصرها، فخلق امتداد حركتها وجسمها بريشـة فنان مبدع، فكانت العبارة مادتها والصياغة شكلها، والعاطفة لونها. This study has soughted to show what has the image as a role in embodying the ideas and the things. The semiotic was a base and a definition in this research which is marked with “the dread images in the ENNABIGUA EDDOBIANI poem”. They had focused on the litterature imagine as a strategise for observing the dread imagining beauty side in the poetic speech of the ENNABIGUA ADDOBIANI and cause of cooperating the builder secondary elements of the image so the concrete sinifeant , which is inspirited from nature ; is reversed to a new sinifeant tries to take a new beauty appearance ; a new colour  and a new meaning also.Through his art; the poet could to observe the human weak moments; so he sounded and pointed his feeling and his heart pulse، and he made the image a live from alternating its elements; he created a continue for its moving so he personified it by a creative artist feather; that the expression was its matter; the reexpression was its shape and the affection was its colour.